2023
DOI: 10.1038/s41598-023-27692-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrate and ammonium on assimilation of nitric oxide by Heterosigma akashiwo

Abstract: The harmful alga Heterosigma akashiwo possesses a hybrid nitrate reductase (NR) enzyme, NR2-2/2HbN, which has the potential to convert NO to nitrate for assimilation into biomass. In previous research, NR transcription in H. akashiwo was induced by nitrate while NR activity was inhibited by ammonium. Here, the capacity of H. akashiwo to use NO in the presence of nitrate and/or ammonium was investigated to understand the regulation of NO assimilation. Continuous cultures of H. akashiwo were acclimated to growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Recently, Healey et al (2023) proposed that utilization of nitric oxide (NO) may give H . akashiwo a competitive advantage over other phytoplankton in regions with high NO concentrations [ 16 ]. According to the physiological strategies of HAB species, including nutrient acquisition styles, behaviors, and biological interactions with coexisting species, Jeong et al (2015) categorized the HAB dynamics into four generation mechanisms (GMs; GM1–GM4), and GM4 can be used to explain the bloom of H .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Healey et al (2023) proposed that utilization of nitric oxide (NO) may give H . akashiwo a competitive advantage over other phytoplankton in regions with high NO concentrations [ 16 ]. According to the physiological strategies of HAB species, including nutrient acquisition styles, behaviors, and biological interactions with coexisting species, Jeong et al (2015) categorized the HAB dynamics into four generation mechanisms (GMs; GM1–GM4), and GM4 can be used to explain the bloom of H .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research identified novel NRs with alternative structures in C. subsalsa and Heterosigma akashiwo (Raphidophyceae) (Stewart and Coyne, 2011;Wang et al, 2018; Figure 1). NR2-2/2HbN (referred to hereafter as NR2) identified in C. subsalsa and H. akashiwo has a 2/2 hemoglobin (2/2Hb) domain inserted in the Hinge-2 region that has been proposed to confer nitric oxide dioxygenase activity to this enzyme (Stewart and Coyne, 2011;Healey et al, 2023). Following research identified another novel NR in C. subsalsa (NR3) (Wang et al, 2018).…”
mentioning
confidence: 99%